第53次日本南極地域観測隊気象部門報告2012 - 藤田, 建; フジタ, タツル; 大吉, 智也; オオヨシ, トモヤ; 清水, 悟; シミズ, サトル; 蓜島, 宏治; ハイジマ, コウジ; 坂梨, 貴将; サカナシ, タカマサ; Fujita, Tatsuru; Oyoshi, Tomoya; et al. (国立極地研究所, 2018)
この報告は第53次日本南極地域観測隊気象部門が，2012年2月1日～2013年1月31日まで昭和基地において行った気象観測結果をまとめたものである．観測方法，測器，統計方法等は第52次隊とほぼ同様である．越冬期間中の特記事項としては，次のものが挙げられる． 1）冬期と越冬明けの夏期の気温の差が大きかった．冬期は5月25日に気温が－40℃を下回り5月としてはじめて－40℃以下を観測した．9月13日には日最低気温－43.9℃となり，低いほうから2位の記録を更新した．越冬明けの夏期は，12月22日に雨を9年ぶりに観測し，2013年1月の月平均気温0.8℃が高いほうから2位となり記録を更新した． 2）昭和基地上空の下部成層圏において，1月と2月の月平均気温はおおむね平均より低く，複数の指定気圧面で月平均気温の低いほうからの記録第1位を記録した．一方，2月の対流圏の月平均気温はおおむね平年より高く，複数の指定気圧面で月平均気温の高いほうからの記録第1位を記録した．また，7月から2013年1月にかけて，対流圏から下部成層圏において，おおむね平年より高く推移し，特に11月と2013年1月はいくつかの指定気圧面において月平均気温の高いほうからの記録第1位を記録した． 3）昭和基地上空のオゾン全量は，9月上旬からオゾンホールの目安となる220 m atm-cmを大きく下回ったが，10月には上回ることが多くなり，11月中旬にはオゾン全量は回復した．オゾン全量の回復は，1990年以降では2002年，1994年，2009年に次いで4番目に早かった． This report describes the results of meteorological observations at Syowa Station from February 1st, 2012 to January 31st, 2013, carried out by the Meteorological Observation Team of the 53rd Japanese Antarctic Research Expedition (JARE-53). The observation methods, instruments and statistical methods used by JARE-53 were almost the same as those used by the JARE-52 observation team. Remarkable weather phenomena observed during the period of JARE-53 are as follows. 1) The temperature difference between the winter and the next summer was considerably large. In the winter, the temperature dropped below −40 degrees C on May 25th for the first time in May. The daily minimum temperature of −43.9 degrees C on September 13th updated the record ranking second place. In the next summer, rain was observed for the first time in 9 years, and the monthly mean temperature of 0.8 degrees C on January 2013 updated the record ranking second place. 2) The lower stratosphere monthly mean temperatures during January and February over Syowa Station were almost lower than normals and updated records low for some standard isobaric surfaces. In contrast, the troposphere monthly mean temperatures at February were almost higher than normals and updated records high for some standard isobaric surfaces. In addition, the troposphere and the lower stratosphere monthly mean ...